Design of Prodrugs to Enhance Colonic Absorption by Increasing Lipophilicity and Blocking Ionization - Rebecca Nofsinger; Sophie-Dorothee Clas; Rosa I. Sanchez; Abbas Walji; Kimberly Manser; Becky Nissley; Jaume Balsells; Amrithraj Nair; Qun Dang; David Jonathan Bennett; Michael Hafey; Junying Wang; et al. (MDPI AG, 2014)
Prodrugs are chemistry-enabled drug delivery modifications of active molecules designed to enhance their pharmacokinetic, pharmacodynamic and/or biopharmaceutical properties. Ideally, prodrugs are efficiently converted in vivo, through chemical or enzymatic transformations, to the active parent molecule. The goal of this work is to enhance the colonic absorption of a drug molecule with a short half-life via a prodrug approach to deliver sustained plasma exposure and enable once daily (QD) dosing. The compound has poor absorption in the colon and by the addition of a promoiety to block the ionization of the molecule as well as increase lipophilicity, the relative colonic absorption increased from 9% to 40% in the retrograde dog colonic model. A combination of acceptable solubility and stability in the gastrointestinal tract (GI) as well as permeability was used to select suitable prodrugs to optimize colonic absorption.